Theoretical study of a new oxazolidine -5- one derivative as a corrosion inhibitor for carbon steel surface - Kubba, Rehab Majed; Al-Joborry, Nada Mohammed (Iraqi Journal of Science, 2021)
A newly derivative of oxazolidin-5- one namely [2-(2-biphenyl-4-yl-imidazo [1,2-a] pyridine-3-yl)-3-(4-nitro-phenyl)-oxazolidin-5-one (BIPNO5)] was examined as an corrosion inhibitor for carbon steel surface. Quantum mechanical method of Density Functional Theory (DFT) with (B3LYP (6-311++G (2d, 2p)) level of theory was used to calculate the minimize structure, physical properties and inhibition chemical parameters, in vacuum and two solvents (DMSO and H2O), all at equilibrium geometry. The results indicated that the new derivative could adsorb on the surface of carbon steel through the heteroatom, showing that the new inhibitor has good corrosion inhibition performance.